The Syenite–Carbonatite Complex of Ihouhaouene (Western Hoggar, Algeria): Interplay Between Alkaline Magma Differentiation and Hybridization of Cumulus Crystal Mushes - Djeddi, A.; Parat, F.; Bodinier, J.-L.; Ouzegane, K.; Dautria, J.-M. (Frontiers in Earth Science, 2021)
The 2 Ga-old Ihouhaouene alkaline complex (Western Hoggar, Algeria) is among the oldest known carbonatite occurrences on Earth. The carbonatites are calciocarbonatites hosted by syenites, the predominant rock type in the complex. Both rock types are characterized by medium grained to pegmatitic textures and contain clinopyroxene, apatite, and wollastonite, associated with K-feldspar in syenites and a groundmass of calcite in carbonatites. The rock suite shows a continuous range of compositions from 57-65 wt.% SiO2 and 0.1-0.4 wt.% CO2 in red syenites to 52-58 wt.% SiO2 and 0.1-6.5 wt.% CO2 in white syenites, 20-35 wt.% SiO2 and 11-24 wt.% CO2 in Si-rich carbonatites (>10% silicate minerals), and <20 wt.% SiO2 and 24-36 wt.% CO2 in Si-poor carbonatite (<5% silicate minerals). Calculation of mineral equilibrium melts reveal that apatite and clinopyroxene are in disequilibrium with each other and were most likely crystallized from different parental magmas before being assembled in the studied rocks. It is subtle in the red syenites, whereas the white syenites and the Si-rich carbonatites bear evidence for parental magmas of highly contrasted compositions. Apatite was equilibrated with LREE-enriched (Ce/Lu=1690-6182) carbonate melts, also characterized by elevated Nb/Ta ratio (>50), whereas clinopyroxene was precipitated from silicate liquids characterized by lower LREE/HREE (Ce/Lu=49-234) and variable Nb/Ta ratios (Nb/Ta=2-30). The Si-poor carbonatites resemble the Si-rich carbonatites and the white syenites with elevated REE contents in apatite equilibrium melts compared to clinopyroxene. However, apatite equilibrium melt in Si-poor carbonatite shows a majority of subchondritic values (Nb/Ta<10) and clinopyroxene have chondritic to superchondritic value (Nb/Ta=15-50). Although paradoxical at first sight, this Nb-Ta signature may simply reflect the segregation of the carbonatite from highly evolved silicate melts characterized by extremely low Nb/Ta values. Altogether our results suggest an evolutionary scheme whereby slow cooling of a silico-carbonated mantle melt resulted in the segregation of both cumulus minerals and immiscible silicate and carbonate melt fractions, resulting in the overall differentiation of the complex. This process was however counterbalanced by intermingling of partially crystallized melt fractions, which resulted in the formation of hybrid alkaline cumulates composed of disequilibrium cumulus phases and variable proportions of carbonate or K-feldspar.